Downhole measurement: MWD - Abdul Razak, Mohd. Razif (Faculty of Chemical & Natural Resources Engineering, 1991)
Measurement While Drilling (MWD) now becoming an important method of measuring the downhole parameters and transmitting the informations to the surface while drilling in operation at almost real time. The most important application of MWD is for directional drilling, where its eliminates the downtime for directional survey. This paper discussed the engineering aspect s of the technology and examples of the applications and future developments of MWD